1965
DOI: 10.1071/bi9650379
|View full text |Cite
|
Sign up to set email alerts
|

The Variation in the Composition of Milk During Successive Stages of Milk Removal from the Mammary Gland of the Cow

Abstract: SummaryThe composition of milk samples obtained during the milking period and following the injections of oxytocin has been determined in an attempt to elucidate the role of the epithelium of the ducts and cisterns in milk secretion.The results showed that the concentration of sodium and chloride in whey increased up to 29% with the successive samples, while the concentration of lactose, citrate, phosphate, calcium, and magnesium in whey and protein, calcium, and magnesium in skim milk decreased 12-24%. The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1965
1965
1985
1985

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 4 publications
1
7
0
Order By: Relevance
“…The possible effect of oxytocin on the composition of the milk secreted was discussed by Mackenzie and Lascelles (1965). It is not possible from the present data to attribute any specific effect of oxytocin on milk secretion.…”
Section: Discussionmentioning
confidence: 46%
See 3 more Smart Citations
“…The possible effect of oxytocin on the composition of the milk secreted was discussed by Mackenzie and Lascelles (1965). It is not possible from the present data to attribute any specific effect of oxytocin on milk secretion.…”
Section: Discussionmentioning
confidence: 46%
“…Some water absorption probably occurred from the high sodium chloride solutions either as a result of the further lowering of the osmotic pressure by the absorption of sodium chloride or as a result of a closer link between the absorption of water and that of sodium. The failure to demonstrate significant absorption of water was unexpected since normal milk is isotonic with blood (Jenness and Patton 1959) and the results of the experiments by Mackenzie and Lascelles (1965) had indicated that the absorption of water from alveolar milk occurred as it passed through the ducts and cisterns.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In estimating the rate of secretion of milk, bias due to residual carry-over can be eliminated by removing the residual milk following injection of oxytocin at the end of the normal milking procedure so as to obtain a second ejection of milk. A limitation of this method is that the administered oxytocin may affect the rate of secretion of milk (Morag, 1968) or its composition (Mackenzie & Lascelles, 1965;Wheelock, Rook & Dodd, 1965a). However, Linzell (1967) considers that these results may be due to the high doses of oxytocin used since he found that in goats the composition of the milk was not affected by lower doses.…”
mentioning
confidence: 90%